Heavy metals in equine biological components - Souza,Maria Verônica de (2014)
The objective of this research was to determine the concentration of heavy metals in the blood (Pb, Ni and Cd), serum (Cu and Zn) and hair (Pb, Ni, Cd, Cu and Zn) of horses raised in non-industrial and industrial areas (with steel mill), and to verify the possibility to use these data as indicators of environmental pollution. The samples were collected during summer and winter, aiming to verify animal contamination related to environment and season of the year. Copper and Zn contents determined in the serum and Cd and Ni contents obtained in the blood indicated no contamination effects of industries. For some animals, contents of Pb in the blood were higher than those considered acceptable for the species, but without relationship with industrialization and without clinical signs of Pb intoxication. The heavy metals evaluated on the hair of horses in this study were not increased with the presence of industries, but Cu and Cd contents were influenced by the season. The contents of some heavy metals in biological components analyzed were influenced by season sampling; however, serum, blood and hair may not be suitable to indicate differences in environmental contamination between the two contrasting areas. Most part of the heavy metal contents was lower or close to the reference values for horses. Serum, blood and hair components from horses may not be effective as indicators of environmental pollution with heavy metals. Industrialization and seasons have no effects on most part of heavy metals contents from those components.